2021
DOI: 10.3389/fnagi.2021.636545
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between the Gut Microbiota and Parkinson's Disease, a Meta-Analysis

Abstract: Patients with Parkinson's disease (PD) were often observed with gastrointestinal symptoms, which preceded the onset of motor symptoms. Neuropathology of PD has also been found in the enteric nervous system (ENS). Many studies have reported significant PD-related alterations of gut microbiota. This meta-analysis was performed to evaluate the differences of gut microbiota between patients with PD and healthy controls (HCs) across different geographical regions. We conducted a systematic online search for case-co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
116
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(118 citation statements)
references
References 62 publications
2
116
0
Order By: Relevance
“…Further, Akkermansia muciniphila and Bifidobacterium , abundant inhabitants of the human gut, can degrade mucin ( Derrien et al., 2008 ; Ruas-Madiedo et al., 2008 ). Several studies on gut microbiota in PD have shown increases in the relative abundance of these bacteria ( Chiang and Lin, 2019 ; Shen et al., 2021 ). Bifidobacteria are commonly available as commercial products, and their abundance in the gut is reported to correlate to the levodopa dose in PD ( Wallen et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Further, Akkermansia muciniphila and Bifidobacterium , abundant inhabitants of the human gut, can degrade mucin ( Derrien et al., 2008 ; Ruas-Madiedo et al., 2008 ). Several studies on gut microbiota in PD have shown increases in the relative abundance of these bacteria ( Chiang and Lin, 2019 ; Shen et al., 2021 ). Bifidobacteria are commonly available as commercial products, and their abundance in the gut is reported to correlate to the levodopa dose in PD ( Wallen et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Since 2015, changes in gut microbiota compositions in PD have been found in several large-scale case-control studies ( Scheperjans et al., 2015 ; Shen et al., 2021 ). Composition changes concerning the phylum level are difficult to establish due to high variability in the relative abundances of bacterial phyla in PD studies ( Chiang and Lin, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, PD is characterized by the dysregulation of the dopamine system [ 60 ]. Increase of Akkermansia , Catabacter , Lactobacillus , Bifidobacterium , Bifidobacteriaceae, Ruminococcaceae, Verrucomicrobiaceae, Christensenellaceae, and decrease of Roseburia , Faecalibacterium, Lachnospiraceae ND3007 group, Prevotellaceae, Blautia , Coprococcus , and Lachnospira have been observed in PD patients [ 17 , 90 , 91 ]. The metabolism of l -DOPA and dopamine is associated with the abundance of Enterococcus faecalis in patients with PD [ 92 ].…”
Section: Influence Of Gut Microbe-regulated Neurotransmitter Synthesis On Cognitionmentioning
confidence: 99%
“…According to the analysis, the relative abundance of this ora in patients with SLE is higher than that in healthy people. The result might indicate that there may be bacteria can reconstruct gut homeostasis by potential compensatory regulation [42,51] . Furthermore, there was no signi cant difference in Lachnospiraceae and Bacteroides between SLE patients and healthy controls in the included study.…”
Section: Meta-analysis Resultsmentioning
confidence: 99%